1994
DOI: 10.3109/00365529409090469
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Vagotomy in the Rat: Effects on Bone and Mineral Metabolism

Abstract: Highly selective vagotomy (HSV) or sham operation was performed in male rats. Fifteen weeks later bone mineralization, fractional intestinal absorption and balance, urinary excretion, and serum levels of calcium, magnesium and phosphorus, together with serum gastrin, parathyroid hormone, calcitonin, vitamin D metabolites, osteocalcin, isoenzymes of alkaline phosphatase, and the urinary excretion of cyclic AMP and hydroxyproline were assessed. HSV induced chronic hypergastrinemia and enhanced the weight of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…16 In another study in the rat, it has been demonstrated that highly selective vagotomy, which normally blocks stomach acid production, does not interfere with body weight, food intake, intestinal resorption, mineral balance, and bone mineralization, while serum PTH levels and urinary hydroxyproline excretion increase. 17 Moreover, these observations argue against a role of gastric acidity in intestinal calcium resorption and are in favor of less efficient intestinal calcium resorption after vagotomy. In another rat study, it was elegantly shown that Gx evokes hyperphosphaturia and increases of cyclic AMP levels in the presence of persistent normal serum PTH levels.…”
Section: Estrogen-deprived Bone Loss Versus Gastrectomy-evoked Bone Lossmentioning
confidence: 98%
“…16 In another study in the rat, it has been demonstrated that highly selective vagotomy, which normally blocks stomach acid production, does not interfere with body weight, food intake, intestinal resorption, mineral balance, and bone mineralization, while serum PTH levels and urinary hydroxyproline excretion increase. 17 Moreover, these observations argue against a role of gastric acidity in intestinal calcium resorption and are in favor of less efficient intestinal calcium resorption after vagotomy. In another rat study, it was elegantly shown that Gx evokes hyperphosphaturia and increases of cyclic AMP levels in the presence of persistent normal serum PTH levels.…”
Section: Estrogen-deprived Bone Loss Versus Gastrectomy-evoked Bone Lossmentioning
confidence: 98%
“…The findings of this experimental model are similar to those of senile osteoporosis. Common findings in total gastrectomized rats are decreases in both cortical and cancellous bone mass (15,18,34,39), anemia (29) and reduced intestinal calcium absorption (27). Furthermore, our preliminary experiment using this model exhibits hyperparathyroidism and an elevation of 1,25-dihydroxyvitamin D in blood.…”
Section: Fos and Bonementioning
confidence: 95%
“…(11) Common findings in GX rats include decreased bone mass, (1214) anemia, (15) and decreased intestinal calcium (Ca) absorption. (16) …”
Section: Introductionmentioning
confidence: 99%